Internal structure and water routing of an ice-debris landform assemblage using multiple geophysical methods in the semiarid Andes - Navarro, Gonzalo; Valois, Rémi; MacDonell, Shelley; de Pasquale, Giulia; Díaz, Juan Pablo (Frontiers in Earth Science, 2023)
Rock glaciers are the most abundant (peri)glacial landform in the semiarid Andes (SA, 29-34°S), covering about three times the area of mountain glaciers. Recent studies suggest they may play an important hydrological role, including generating, storing and routing water. However, processes governing these roles are still poorly known especially for glacier complex units, i.e., where there is a juxtaposition or continuity of different (peri)glacial landforms, which are common in semiarid Andean and Himalayan areas. This study aims to understand how the internal structure of an ice-debris landform assemblage controls hydrological routing. To address this aim, we used a combination of three geophysical techniques to qualitatively determine the internal structure and favourable water routing and storage zones at the Tapado glacier complex (30°S), Chile. The Tapado glacier complex consists of an assemblage of a debris-free glacier, a debris-covered glacier and two rock glaciers. For the purpose of this study, we focused on the debris-covered and active rock glacier connection. At this site, the debris-covered glacier has a relatively thin debris-cover that increases thickness downglacier. This debris cover connects to the active rock glacier and forms the active layer. The rock glacier contains a heterogenous internal structure consisting of debris with water or segregated ice filling the voids, which likely derives from the massive ice of the debris-covered glacier. The superficial debris layer of the ice-debris landforms may act as a transmissive medium by routing water downstream above the massive ice of the debris-covered glacier, but also into deeper areas, as intra-permafrost flow, in the rock glacier. The rock glacier likely has a higher capacity to transmit vertical and horizontal flows, thereby enhancing infiltration processes. This study reinforces the value of geophysical methods to determine the internal structure of ice-debris landforms, particularly in the transition between landforms, and highlights how a warming climate and consequent paraglacial processes will impact the hydrological system not only in terms of water storage, but also water transfer.